STRATEGI MENUJU WORLD CLASS UNIVERSITY (WCU) PADA UNIVERSITAS SEMARANG - S Susanto (Jurnal Transformatika, 2014)
University Semarang (USM) is now 26 years old (founded in 1987). It stands to USM achievement, both national and international. Although at the regional level in Central Java USM has become the leading private universities, but at the national level has not been fully encouraging, let alone the world level.Academically, USM is not yet in a world university ranking methods, such as: Academic Ranking of World Universities (ARWU), The Times Higher Education Supplement (THES) and Webometrics. Only in Webometric lah, world university ranking USM entered electronically although not entirely encouraging. Apparently, we need to work harder in order to reach World Class University category.